2015
DOI: 10.1002/oti.1420
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Risk Signals as a Screening Tool for Early Identification of Sensory Processing Disorders

Abstract: The main purpose of this research was to determine if the indicators of risk included in the Indicators of Developmental Risk Signals (INDIPCD-R) could differentiate between children at risk of sensory processing disorders (SPDs) from those with normal development and if the SPD indicators correlated with a delay or altered development. A retrospective, descriptive, correlational design was used with a sample of 51 children, 36 referred because of clinical sensory processing indicators and 15 with non-clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…It has been observed that the sensory symptoms of school-aged children with autism are affected by the degree of cognitive maturity of the children ( 9 , 20 ). A strong and positive correlation has also been observed between difficulties in sensory processing and executive function deficits in various populations, such as premature children ( 21 23 ), children with ASDs ( 24 26 ), and children with attention deficit hyperactivity disorder (ADHD) ( 27 29 ). These results show that difficulties associated with sensory processing and executive functions tend to be related to each other.…”
mentioning
confidence: 99%
“…It has been observed that the sensory symptoms of school-aged children with autism are affected by the degree of cognitive maturity of the children ( 9 , 20 ). A strong and positive correlation has also been observed between difficulties in sensory processing and executive function deficits in various populations, such as premature children ( 21 23 ), children with ASDs ( 24 26 ), and children with attention deficit hyperactivity disorder (ADHD) ( 27 29 ). These results show that difficulties associated with sensory processing and executive functions tend to be related to each other.…”
mentioning
confidence: 99%